Sistem Kendali Pintu Gerbang dengan Menggunakan Bluetooth Android - Ariyono Setiawan; Yuyun Suprapto; Totok Warsito (Jurnal Penelitian)
There are less constraints responded a remote device that is controlled by conventional control (still using infrared as a transmission medium). This led the creation of new control system which utilizes Bluetooth as a medium of communication. The working principle of this control system design is to use a cell phone as a microcontroller as remotnya and data processing and control. The design is driven by a series of minimum ATMega system with IC 16 as a processor and controller